Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð½Ð° Ð´Ð¸Ñ„Ñ„ÐµÑ€ÐµÐ½Ñ†Ð¸Ñ€Ð¾Ð²Ð¾Ñ‡Ð½Ñ‹Ðµ ÑÐ²Ð¾Ð¹ÑÑ‚Ð²Ð° Ð¼ÐµÐ·ÐµÐ½Ñ…Ð¸Ð¼Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÑÑ‚Ñ€Ð¾Ð¼Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº-Ð¿Ñ€ÐµÐ´ÑˆÐµÑÑ‚Ð²ÐµÐ½Ð½Ð¸ÐºÐ¾Ð² Ñ„ÐµÑ‚Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ð¸ ÐºÐ¾ÑÑ‚Ð½Ð¾Ð³Ð¾ Ð¼Ð¾Ð·Ð³Ð° Ð²Ð·Ñ€Ð¾ÑÐ»Ð¾Ð³Ð¾ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Skorobogatova, N. G.; Petrenko, Yu. A.; Volkova, N. A.; Petrenko, A. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
The cryopreservation influence on osteogenic and adipogenic capacities of expanded in vitro mesenchymal stromal cells derived from human fetal liver and adult bone marrow was investigated. Saving proliferative ability and differentiation potential of the progenitor cells after cryopreservation by 2-step slow freezing under Me2SO protection was shown.